ANALISIS KUALITAS LAYANAN PASIEN TUBERKULOSIS DI POLI PARU RUMAH SAKIT UMUM DAERAH dr. SOEROTO NGAWI TAHUN 2021 - Ririn Noviyanti; Nur Widiastuti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2021)
This study aims to determine and analyze the quality of services expected and provided to tuberculosis patients and to formulate efforts to improve the quality of services for tuberculosis patients at the Lung Poly, Regional General Hospital, dr. Soeroto, Ngawi Regency. This research is a qualitative descriptive study using 112 tuberculosis patients in the pulmonary polyclinic of RSUD. dr. Soeroto Ngawi as the respondent. Based on the data analysis, it was obtained that the patient expectation was 34.88 and the reality score was 30.16 with a gap of 4.73. The patient satisfaction index on the quality of service at the Pulmonary Polyclinic of the Regional General Hospital dr. Soeroto Ngawi Regency is in the satisfied category. Efforts that can be formulated to improve service quality include: Health workers need to improve the delivery of information related to activities and behavior to patients so that they can maximize treatment and minimize transmission. Standard Operating Procedure is needed regarding information that needs to be conveyed to patients and socialization to health workers so that misinformation can be minimized. Provision of written information through various media that is easily accessible to patients is needed, health workers need to increase the use of Personal Protective Equipment as an effort to prevent transmission and minimize the risk of infection, especially for health workers along with SOPs for supervision from management to improve the compliance of health workers in the use of Personal Protective Equipment. Health workers need to improve physical appearance, neatness to improve the quality of service to patients and increase alertness in services, especially in the registration section. The hospital needs to improve the quality of services, especially the registration section so that it can improve the quality of services provided and according to patient expectations. The hospital can organize and involve human resources in various trainings such as communication training, excellent service to improve the quality of service to patients. Supervision is needed regarding services to tuberculosis patients, especially in the registration section by the person in charge and the head of the room so that the quality of service can be optimal.